"Horned cattle and pack horses": zooarchaeological legacy collections from the unauthorized (and unscreened) Spanish Fort. Issue 3 (2nd September 2018) - Pavao-Zuckerman, Barnet; Mayfield, Tracie; Copperstone, Chance; Foster, H. Thomas
ABSTRACT: In 1689, the governor of La Florida ordered the construction of a fort near the Muscogee (Creek) ancestral community of Apalachicola, supplying it with a caravan of "horned cattle and pack horses." The fort, referred to as "Spanish Fort, " was abandoned a year later. Archaeological investigations of the fort were carried out in 1960 without sieving, and a large collection of faunal remains was minimally studied. Despite the limitations of the recovery methods, a recent analysis of these zooarchaeological legacy collections provides insight into the provisioning strategies of the Spanish military 150 years after initial colonialism began. Spanish Fort was better provisioned than its predecessors, such as Fort San Juan, but with a limited range of domesticated livestock—only cattle and horses. The presidio may have traded with the Apalachicola community in order to diversify their diet, but butchering marks indicate that the presidio's soldiers processed their own meat at the fort. Having learned hard lessons from earlier colonial expeditions, Spanish military colonialists minimized the outpost's vulnerability by not relying heavily on the local Native American population, while building a transactional relationship with Apalachicola to ensure the community's cooperation. The zooarchaeological materials from Spanish Fort also indicate that the fort was intentionally destroyed by fire, providing a glimpse of Spanish adaptive strategies as the mission of securing the inland Southeast from rival colonialism abruptly ended.